2018
DOI: 10.1101/443325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of a simple and novel cut-point based CSF and MRI signature for predicting Alzheimer’s disease progression that reinforces the 2018 NIA-AA research framework

Abstract: The 2018 NIA-AA research framework proposes a classification system with beta-Amyloid deposition, pathologic Tau, and neurodegeneration (ATN) for the diagnosis and staging of Alzheimer’s Disease (AD). Data from the ADNI (AD neuroimaging initiative) database can be utilized to identify diagnostic signatures for predicting AD progression, and to determine the utility of this NIA-AA research framework. Profiles of 320 peptides from baseline cerebrospinal fluid (CSF) samples of 287 normal, mild cognitive impairmen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
(36 reference statements)
2
5
0
Order By: Relevance
“…Figures 1A-D recapitulates previous analyses by us and others [33, 4749] showing that Aβ1-42, tTau, pTau-181 and HV are all significantly different in NL and AD subjects and that these values are intermediate for MCI subjects. For all four markers in Figures 1A-D, comparisons of the means between NL and AD groups reveal highly significant differences (p<0.0001 in all cases).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Figures 1A-D recapitulates previous analyses by us and others [33, 4749] showing that Aβ1-42, tTau, pTau-181 and HV are all significantly different in NL and AD subjects and that these values are intermediate for MCI subjects. For all four markers in Figures 1A-D, comparisons of the means between NL and AD groups reveal highly significant differences (p<0.0001 in all cases).…”
Section: Resultssupporting
confidence: 87%
“…Methods and data used for this research are similar to those used in Devanarayan et al [33]. The ADNI database (adni.loni.usc.edu) utilized in this research was launched in 2003 as a public-private partnership, led by Principal Investigator Michael W. Weiner, MD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods and data used for this research are similar to those used in Devanarayan et al [33]. The ADNI database (adni.loni.usc.edu) utilized in this research was launched in 2003 as a publicprivate partnership, led by Principal Investigator Michael W. Weiner, MD.…”
Section: Methodsmentioning
confidence: 99%
“…CC-BY 4.0 International license a certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made available under The copyright holder for this preprint (which was not this version posted January 7, 2019. ; https://doi.org/10.1101/512939 doi: bioRxiv preprint 5 studies involving hypothesis-free approaches to identify optimal peptides to include in biomarker signatures [20,33,34], the current study was focused on the utility of VGF. Using data from two independent groups in the ADNI cohort: one group of AD and control subjects and a separate group of MCI subjects, it was found that VGF, when combined with conventional biomarkers, enhanced both the diagnostic accuracy of these markers and the ability of these markers to predict MCI to AD conversion.…”
Section: Introductionmentioning
confidence: 99%